Kualitas Akrual: Kebutuhan Stakeholder dan Konsekuensi Ekonomi - Sri Novita; Nurzi Sebrina (Universitas Negeri Padang, 2022)
This study aims to examine the quality of accrual having economic consequences in predicting future cash flows in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX), the research sample was determineted using the pusposive sampling method with a total sample of 213 companies. The data used is secondary data from the company’s annual report. The analytical method used i multiple regression analysis (MRA). The result showed that the interest of investors and the interest of lenders were positively correlated with the quality of accruals. Suppliers interest is negatively correlated with accrual quality. While the quality of accruals has economic consequences in predicting future cash flows.